Pemikiran dan perjuangan Mohammad Natsir - Taher, Tarmizi (Jakarta : Pustaka Firdaus, 1996)
Thoughts of Mohammad Natsir, 1908-1993, the former Indonesian prime minister on Indonesian politics and religion; seminar papers.
Keywords: Natsir, M., -- 1908-1993 -- Political and social views -- Congresses; Natsir, M., -- 1908-1993 -- Views on Islam -- Congresses; Islam -- Indonesia -- Congresses